1996
DOI: 10.1002/hep.510240308
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Hepatitis: Analysis of 27 Cases and Comparison With Acute Viral Hepatitis

Abstract: have been involved in the course of enteric fever, resulting The liver is commonly involved in patients with tyin a wide array of presentations. 2 Abnormalities of liver biophoid fever. However, severe hepatic derangement simchemical tests are commonly found in patients with typhoid ulating acute viral hepatitis is rare. Our aim was to charfever. 3 However, a picture of hepatitis with fever and frank acterize the clinical picture, biochemical features, and jaundice characterizes the course of a small subset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 9 publications
2
28
0
1
Order By: Relevance
“…The presentation with marked elevation of transaminases similar to that of acute viral hepatitis, as observed in this case, has been reported by others. [8910] Recognition of this clinical condition is particularly important in tropical countries where malaria and viral hepatitis are quite common. El-Newihi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presentation with marked elevation of transaminases similar to that of acute viral hepatitis, as observed in this case, has been reported by others. [8910] Recognition of this clinical condition is particularly important in tropical countries where malaria and viral hepatitis are quite common. El-Newihi et al .…”
Section: Discussionmentioning
confidence: 99%
“…El-Newihi et al . [9] did a retrospective analysis to compare clinical, biochemical picture, and the outcome of patients with Salmonella hepatitis and acute viral hepatitis. They concluded that the clinical picture of Salmonella hepatitis is frequently indistinguishable from that of viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The principal clinical syndromes associated with Salmonella infection range from selflimited gastrointestinal infections to systemic infections (7). Recently, acute liver injury has been reported in humans infected with Salmonella enterica serovar Typhi through the oral route, and this condition has been termed Salmonella hepatitis; patients usually present with hepatomegaly and a moderate elevation in transaminase levels (8,9).…”
mentioning
confidence: 99%
“…Therefore, these 2 diseases may occur simultaneously. It has been reported that the ratio of ALT to LDH may distinguish hepatitis caused by Salmonella (<4.0) and acute viral hepatitis (>5.0) [15], and the ration here was 4.13. When the patient was examined upon admission to our hospital, it is likely that his aminotransferase levels had already decreased because hepatitis A is usually a self-limiting illness.…”
Section: Discussionmentioning
confidence: 56%